2002
DOI: 10.1080/10903120290938698
|View full text |Cite
|
Sign up to set email alerts
|

R Epeat Ems T Ransports Among E Lderly E Mergency D Epartment P Atients

Abstract: Repeaters accounted for 18% of elderly ED patients transported by EMS and 40% of elderly transports to the authors' ED. There were significantly fewer trauma transports in the repeater group. One-half of the repeaters returned only once in a 12-month period and a third of these occurred more than three months apart. It is important to understand the characteristics of elderly EMS repeaters in order to use this opportunity for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 26 publications
(31 reference statements)
1
9
2
Order By: Relevance
“…Our results were slightly lower than the 78% reported in a urban study 9. This difference may be due to methodological differences as Weiss et al based their calculations on patients transported to a single institution while this study was community-based.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Our results were slightly lower than the 78% reported in a urban study 9. This difference may be due to methodological differences as Weiss et al based their calculations on patients transported to a single institution while this study was community-based.…”
Section: Discussioncontrasting
confidence: 84%
“…Investigators seeking to study prehospital care often must estimate the proportion of emergency medical services (EMS) requests that arise from unique subjects, or individuals making their first request of EMS services during a study period. For many studies, subjects cannot be repeatedly enrolled in the study protocol; therefore, using unadjusted EMS case volumes would significantly over-estimate the number of eligible subjects 9, 10. The over-estimation problem may be further exacerbated when recruitment is limited to older adults (age≥65) because of their relatively high rates of EMS use, which may increase the probability of repeat use 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study by Shah et al, only 70% of EMS calls over a 16 month period for community dwelling elders were for unique individuals 28. Compared with other studies of EMS use by the elderly, our study found that our trauma patients had a higher rate of repeat EMS use within a year of their index visit (37%) than a sample of elders presenting to the emergency department by EMS for all causes studied by Weiss et al (23%) 29. While this might suggest that injury results in a higher need for subsequent EMS care, Weiss et al's study included patients who were sent home from the emergency department and were therefore less sick than our cohort of admitted patients.…”
Section: Discussioncontrasting
confidence: 71%
“…[11][12][13][14] This may be due to the fact that older adults with high comorbidity (>3 chronic conditions) report poorer health, take more prescription medications and have the highest rate of healthcare visits. 15 Data from Hamilton Paramedic Service indicate that tenants in 'seniors' buildings' in underserved areas of lower socioeconomic status in Hamilton, a medium sized city in Canada, with a population of just over 500 000 people, are the most frequent callers to the emergency 911 medical service.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%